A Patient with Henoch-Schönlein Purpura with Intussusception and intractable Nephritis - Min Kyoung Seo; Jeong Hong; Hyun Ee Yim; Ki Soo Pai (Korean Society of Pediatric Nephrology, 2016)
Henoch-Schönlein purpura (HSP) is the most common vasculitis in children, mainly affecting the small vessels of the skin, joints, gastrointestinal tract, and kidneys. Although most cases of HSP resolve spontaneously without sequelae, serious nephrological and intestinal problems may occur in some cases. We experienced a case of HSP complicated by simultaneous intussusception and nephritis in a 14-year-old boy who developed a sudden abdominal pain and gross hematuria on the 11th day after onset of the disease. Imaging studies revealed intussusception that required emergency laparotomy. Despite treatment with steroid and angiotensin-converting enzyme inhibitors, nephritis and nephrosis progressed for 4 weeks, and renal biopsy was performed to confirm the diagnosis. Cyclosporin A therapy was started, and remission of proteinuria was achieved after 5 months. However, the nephritis recurred and worsened to end-stage renal failure during 15 years of follow-up.